Pengaruh Citra Merek dan Kualitas Produk terhadap Keputusan Pembelian Kendaraan Hybrid Toyota di Era Transisi Energi Ramah Lingkungan : Studi Kasus pada Konsumen di Kota Karawang - Huda, Fatkhan Fahmi; Ramadhan, Fajar (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to determine the influence of brand image and product quality on purchasing decisions of Toyota hybrid vehicles in Karawang City during the transition to environmentally friendly energy. The research employed a quantitative method with a survey approach involving 85 respondents, and the data were analyzed using multiple linear regression with SPSS version 26. The sampling technique used was purposive sampling. The results indicate that both brand image and product quality have a positive and significant effect on purchasing decisions. These findings highlight the importance of strengthening brand image and improving product quality to attract consumers to hybrid vehicles.
Keywords: Brand Image; Product Quality; Purchasing Decision